1970
DOI: 10.1017/s0022112070001842
|View full text |Cite
|
Sign up to set email alerts
|

The transient motion of a floating body

Abstract: An analytical method of calculating the body motion was given in an earlier paper. Viscosity and surface tension were neglected, and the equations of motion were linearized. It was found that, for a half-immersed horizontal circular cylinder of radius a, the vertical motion at time τ(a/g)½ is described by the functions h1(τ) (for an initial velocity) and h2(τ) (for an initial displacement) where \begin{eqnarray*} h_1(\tau) &=& \frac{1}{2\pi}\int_{-{\infty}}^{\infty}\frac{e^{-iu\tau}du}{1-\frac{1}{4} \pi u^2(1+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
32
0
1

Year Published

1982
1982
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 4 publications
8
32
0
1
Order By: Relevance
“…For freely floating bodies, the convergence of the algorithm is studied for various amplitudes of motion in free decay tests. We find that the implicit method of van Daalen (1993) and Tanizawa (2000) gives a satisfactory agreement with the analytical results of Maskell and Ursell (1970). A larger discrepancy, however, is found for large amplitude free decay motions, which indicates the need for developing a way to include viscous effects in the present FNPF model.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…For freely floating bodies, the convergence of the algorithm is studied for various amplitudes of motion in free decay tests. We find that the implicit method of van Daalen (1993) and Tanizawa (2000) gives a satisfactory agreement with the analytical results of Maskell and Ursell (1970). A larger discrepancy, however, is found for large amplitude free decay motions, which indicates the need for developing a way to include viscous effects in the present FNPF model.…”
Section: Discussionsupporting
confidence: 59%
“…In the linear limit, Maskell and Ursell (1970) derived a semianalytical solution of the vertical displacement of the center of mass, x G3 (t) for: (i) a zero initial velocity condition…”
Section: Freely Floating Circular Cylindermentioning
confidence: 99%
See 2 more Smart Citations
“…Using our numerical and experimental results, the natural frequency was defined as its average value given by the motion data excluding those of the initial stage. Our results were then compared with those of the existing investigations such as Maskell and Ursell (1970), Ito (1977) and Yeung (1982) as well as the newly obtained results of Lee (2012). Comparison showed that the natural frequency obtained here agrees well with that of Lee (2012), which was found through the frequency domain analysis.…”
supporting
confidence: 72%